Cost analysis of Pharmacy On Delivery (POD) and Conventional Counter Dispensing (CCD) in Pusat Rawatan Warga (PRW) UMS - Mohd Hanafiah Ahmad Hijazi; Nabilah Ayob; Norhidayah Danial; Suzana Awg Piut; Veshny Ganesan; Holly Girlchy Jastin; Dhinagar Selgal Raddy; Muhammad Suhail Abdul Wali; Catherine Soo Shen Chan; Airy Anak Andrew Atoi; Sharina Mohd Shah; Rafidah Lamit; et al. (Penerbit Universiti Malaysia Sabah, 2025)
As the demand for more efficient and accessible healthcare services grows, pharmacy services are evolving to better meet patient needs, offering distinct advantages and challenges in terms of cost, convenience, and accessibility. Pharmacy delivery, whereby one’s medicine being delivered to the comfort of their home or workplace, is one example of pharmacy services evolution, as compared to a standard dispensing at the clinic. This study aims to determine the cost differences between two pharmacy service models implemented at Pusat Rawatan Warga (PRW), Universiti Malaysia Sabah (UMS): Pharmacy On-Delivery (POD) and Conventional Counter Dispensing (CCD). This cross-sectional study was conducted at Pusat Rawatan Warga (PRW), Universiti Malaysia Sabah (UMS), over a two-week period. We analysed both fixed and variable costs associated with the Conventional Counter Dispensing (CCD) and Pharmacy On-Delivery (POD) services, with a particular focus on personnel and transportation expenses. Descriptive analysis was performed using Microsoft Excel to calculate means and standard deviations. The findings showed the cost of POD averaging RM6.55 per prescription compared to RM3.44 for CCD, while the time taken averaging 9.80 minutes per prescription for POD compared to CCD’s 5.69 minutes per prescription. The delivery process was the primary driver of the total time required for POD prescriptions, accounting for approximately 54% of the total time involved. Despite the higher costs, the popularity of POD has grown steadily, with its adoption increasing from 2.49% in 2022 to 6.70% in 2024. This study highlights the need to balance the higher operational costs of Pharmacy On-Delivery (POD) services with their benefits in enhancing medication adherence and convenience, especially for patients with chronic conditions. To support sustainability, strategic improvements such as optimizing delivery routes, using GPS-based tracking, and adopting computerized Hospital Information Systems (HIS) are recommended. These findings provide critical insights for improving the efficiency and cost-effectiveness of POD services at PRW, UMS, particularly in resource-limited healthcare settings.